(untitled) (Islamic Sciences Journal, 2023)
Concepts and terminology may vary according to the use between language, Sharia, custom and the Qur’an, sometimes contrary to what is said in our time, including the concept of atheism, hence the importance of studying words and concepts in the use of the Qur’an, the research came under the title: Concept Atheism in the Qur’an - an objective explanatory study, in which he highlighted the concept of atheism in the situation and linguistic derivation, and the differences between it and some related words, and then he showed the use of this word in his verses the holy ones by studying their meanings objectively, from books The interpretation of the Qur’an and its meanings, he explained the Qur’anic concept, and the differing interpretations in determining the meaning of the words contained in the holy verses.